Findings across agricultural public expenditure reviews in African countries - Mink, Stephen D. (International Food Policy Research Institute, 2016)
This paper examines whether the consensus reached by the late 2000s among African Union member countries and their external partners on the need to reverse the decades-long decline in spending for essential public goods and services in agriculture has begun to result inimproved levels and quality of national expenditure programs for the sector. It synthesizes evidence from 20 Agriculture Public Expenditure Reviews (Ag PERs) that have been carried out in countries in Africa South of the Saharan (Botswana, Burkina Faso, Cameroon, Chad, Côte d’Ivoire, Democratic Republic of the Congo, Ghana, Guinea, Liberia, Madagascar, Mozambique, Rwanda, Nigeria, Senegal, Sierra Leone, South Africa, Tanzania, Togo, Uganda, and Zambia) with World Bank assistance during 2009–2015. This synthesis focuses on several measures: (1) the level of expenditures on agriculture, with particular reference to the explicit target by African heads of state in the 2003 Maputo Declaration on Agriculture and Food Security (reconfirmed in the Malabo Declaration) to allocate 10 percent of national budgets to the sector; (2) the composition and priorities of expenditures with respect to stated national strategies, evidence of impact, and sustainability; and (3) budget planning and implementation that aims to strengthen public financial management in general, and budget coherence, outputs, outcomes, and supporting mechanisms, such as procurement and audit, in particular. This paper uses Ag PERs to analyze budgetary trends across countries, identifies major expenditure issues, and synthesizes lessons regarding spending efficiency. The analysis results in evidence-based recommendations that address, inter alia, budget planning, budget execution, and monitoring for accountability; the creation of a reliable database; more effective intra-and intersectoral coordination; and the cost-effectiveness of different spending policies for meeting various objectives